2022
DOI: 10.12998/wjcc.v10.i33.12230
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of pretreatment serum ferritin concentration in lung cancer patients: A meta-analysis

Abstract: BACKGROUND The association between pretreatment serum ferritin concentration (SFC) and long-term survival in lung cancer remains unclear now. AIM To identify the prognostic value of pretreatment SFC in lung cancer patients based on current evidence. METHODS The PubMed, EMBASE and Web of Science databases were searched from inception to May 29, 2022 for relevant studies. The primary endpoint was overall survival (OS) and the hazard ratios (HRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Zhou et al observed higher levels of serum ferritin and CRP in patients with lung cancer, and regarding the non-small cell lung cancer (NSCLC) subtype, they measured higher values of these parameters in patients with adenocarcinoma compared to those with squamous cell carcinoma [ 38 ]. Additionally, a meta-analysis showed that increased serum ferritin concentration was significantly associated with worse overall survival [ 39 ]. Some studies have shown elevated levels of ferritin in other types of cancer than lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al observed higher levels of serum ferritin and CRP in patients with lung cancer, and regarding the non-small cell lung cancer (NSCLC) subtype, they measured higher values of these parameters in patients with adenocarcinoma compared to those with squamous cell carcinoma [ 38 ]. Additionally, a meta-analysis showed that increased serum ferritin concentration was significantly associated with worse overall survival [ 39 ]. Some studies have shown elevated levels of ferritin in other types of cancer than lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sFT has also been associated with sarcopenia in patients with gastric cancer [92]. Serum ferritin concentration has been described as a reliable prognostic indicator in other oncologic pathologies, such as multiple myeloma [93], lung cancer [94], and Hodgkin lymphoma [95].…”
Section: Role Of Circulating Ferritin In Health and Diseasementioning
confidence: 99%